Composition and structure regulation of Ruddlesden–Popper perovskite for light-emitting diodes applications. Issue 10 (23rd February 2023) - Chen, Weiwu; Qin, Zhaojun; Neogi, Arup; Wang, Zhiming
Abstract : Ruddlesden–Popper (RP) perovskites have gained increased attention for LED applications due to their tunable band gap, enhanced stability, and excellent charge transfer. We summarize four methods to improve the properties of RP perovskites. Abstract : Among all perovskites, Ruddlesden–Popper (RP) perovskites have gained increased attention for LED applications due to their tunable band gap, enhanced stability, and excellent charge transfer. Over the years, the external quantum efficiency (EQE) of perovskite light-emitting diodes (PeLEDs) has increased from 0.1% to 28%. It is helpful to overview the recent developments to understand the PeLEDs. Four methods that are instrumental in improving its properties are summarized in this work: an additive in perovskite, selection of organic spacers, mixed halide perovskite, and 2D/3D heterostructure perovskite. These strategies are used for realizing high-quality pinhole-free RP perovskites by passivating the defects and synthesizing materials with increased stability to yield high-efficiency perovskite-based LEDs and optoelectronic devices. This review also outlines the challenges and future outlooks of PeLEDs.